2003
DOI: 10.1097/00002030-200309260-00011
|View full text |Cite
|
Sign up to set email alerts
|

Changing patterns of knowledge, reported behaviour and sexually transmitted infections in a South African gold mining community

Abstract: Background: In 1998, a major HIV intervention project was started in a mining community in Carletonville, South Africa. This included community-based peer education, condom distribution, syndromic management of sexually transmitted infections (STI), and presumptive STI treatment for sex workers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 10 publications
5
94
0
Order By: Relevance
“…Vuylsteke et al reported the prevalence of C. trachomatis infection to be 7.1% and 12% respectively for males and females during a survey in rural Mozambique [11]. However, our data correspond with results from other studies in Africa [6,8,[20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Vuylsteke et al reported the prevalence of C. trachomatis infection to be 7.1% and 12% respectively for males and females during a survey in rural Mozambique [11]. However, our data correspond with results from other studies in Africa [6,8,[20][21][22][23][24].…”
Section: Discussionsupporting
confidence: 88%
“…Despite all these efforts, however, biomedical outcome measures showed that after 3 years the project had had no impact on levels of STIs (Williams et al, 2003). The peer educators' role remained a difficult one, as their peers were often suspicious of their motives, or simply had insufficient control over their own sexual encounters to be able to put the peer educators' advice into practice.…”
Section: The Summertown Projectmentioning
confidence: 99%
“…In social terms, it has empowered and mobilised sex workers to run a longstanding sexual health project, with significant impacts on sex workers' safety (Cornish, programmes produce an inconsistent pattern, with small effects on some outcome measures but not others (e.g. Bryan, Robbins, Ruiz & O'Neill, 2006;Merakou & KoureaKremastinou, 2006), and it is not unusual for a programme to achieve no positive health effects at all (Elford, Bolding & Sherr, 2001;Sloan & Myers, 2005;Williams et al, 2003).…”
mentioning
confidence: 99%
“…Four studies from Cote d'Ivoire (Ghys et al 2002), Benin , Bolivia (Levine et al 1998) and South Africa (Williams et al 2003) compared the situation before and after introducing similar combinations of peer education, condom promotion and regular STI care. In South Africa this was part of a larger intervention that also targeted miners and youth.…”
Section: Treatment Of Bacterial Sexually Transmitted Infections Combimentioning
confidence: 99%